(untitled) (The Pakistan Development Review, 1989)
Five major issues can be’identified in the field of educa tion in most developing countries. These are (1) llliteracy, (2) Inefficiencies within the school system which affect school output and the quality of education; (3) the output of the educational system does not match with the requirements of the type of skilled manpower required by the economy; (4) the management of educational systems has become more complex given the growth of knowledge; and (5) resources available for educational purposes are insufficien t. This paper, which is a preliminary study, attempts to undertake a comparative analysiS of the state of education in selected Islamic countries with particular reference to Pakistan in the light of some of the issues mentioned above.’ The objective is not only to gather data on major educational variables in these countries but also to see the relative standing of Pakistan with respect to these countries in the educational field. The first two issues will form the focus of our study and the last issue which deals with resource availability for education will be discussed in the context of public expenditure on education. The inefficiencies within the school system can be examined, to some extent, by looking at enrollment ratios, teacher-pupil ratios and drop-out/repeater rates. The data on the latter are available only for repeater rates and that, too, only for the first level of education.